Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Property and Real Estate yang Terdaftar di Bursa Efek Indonesia - Oktafia, Nur Risma; Akhirruddin, Anita (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of profitability, liquidity and company size on company value in property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. This research uses a quantitative descriptive method using the SPSS application in the data processing process during the research period. The population in the research is property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. The sampling technique used the Purpose Sampling method which resulted in 21 companies being sampled. The data used is secondary data, where profitability, liquidity and company size are independent variables, while company value is the dependent variable. The analysis method in this research uses Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Coefficient of Determination Test, and Hypothesis Test. The results of this research show that profitability has a positive effect on company value, liquidity has a negative effect on company value, and company size has a positive effect on company value.